The epitaph on the monument to Husein-bek - Gainutdinov A.M. (Золотоордынское обозрение)
Research objectives: The purpose of the article is to identify the correct and most complete text of the epitaph on the monument to Husein-bek which was preserved in the cemetery of Chishma workers’ village of the Chishminsky district of the Republic of Bashkortostan. Research materials: The study was conducted on the basis of an analysis of articles and books by epigraphists, photographs of monuments of the 14th century, as well as materials of the author’s epigraphic expedition. Results and scientific novelty: The text of the monument to Husein-bek is currently only partially preserved, so it is no longer possible to read it completely. But on the basis of a duplicate of this monument, made and installed on the initiative of Mufti M. Sultanov, and a monument from Bulgar which is very similar to the monuments of Husein-bek, it was possible to reconstruct its inscriptions. We believe that we have managed to ascertain which words were written on the front and sides of this stone that were missed or incorrectly read by other specialists, as well as to refute the date of Husein-bek’s death proposed by scientist G.V. Yusupov. According to paleographic features, the object studied by us is very similar to other monuments that have been preserved in the Bulgar of the modern Spasky district of the Republic of Tatarstan. Based on this, it is safe to say that the monument was made by Bulgarian-Tatar carvers. Husein-bek himself was a statesman, a native of the unknown settlement of Tarsas, which was located in the territory of Turkestan. The epitaph on the monument to Husein-bek is written in relief handwriting in the Arabic and Tatar languages. In addition to information about the deceased, the stone contains traditional Tatar religious sayings, prayers, and poems.